IMPLEMENTASI PENDEKATAN ROHANI TERAPEUTIK SEBAGAI UPAYA PREVENTIF TERHADAP KENAKALAN REMAJA DI SMA NEGERI 5 MEDAN - Sartika Maria Siregar; Imelda Butarbutar; Riana Lumban Raja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This thesis was supervised by Pdt. Imelda Butarbutar, S.Th., M.Psi., M.Pd., and Pdt. Riana Lumbanraja, S.Th., M.Hum., at the Faculty of Teacher Training and Education (FKIP), HKBP Nommensen University, Medan. This study aims to describe the implementation of a therapeutic spiritual approach as a preventative measure against juvenile delinquency at SMA Negeri 5 Medan. The background of this research is based on the increasing number of juvenile delinquent behaviors.The method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation.The results indicate that a therapeutic spiritual approach through communal prayer, reflective worship, spiritual counseling, and meditation can minimize juvenile delinquency and increase students' self-control and moral awareness.Thus, the therapeutic spiritual approach is effective as a preventive strategy in shaping student character at SMA Negeri 5 Medan.